CRIMINAL OFFENDERS WHO DO NOT UNDERGOING HEALTH QUARANTINE OBLIGATIONS AFTER RETURNING FROM ABROAD DURING COVID-19 PANDEMIC: JURIDICAL REVIEW - Fitri Suciningtyas; Zainul Arifin; Nur Chasanah (EQUALEGUM International Law Journal, 2023)
Background. Indonesia is one of the countries affected by COVID19 virus. The government as the highest policy holder has issued various regulations such as social distancing, work from home (WFH), school from home, closing several public facilities, shopping centers, and health quarantine. The problem with this policy is that many people still do not comply with obligations such as quarantine after traveling abroad. This research purpose was to determine legal offenses for criminal offenders who do not follow health quarantine obligations after returning from abroad during the covid-19 pandemic. Research Method. The research used a normative juridical approach as a literature study and developed also conceptualized as legal research. The legal concept is carried out by reviewing all legal regulations related to the legal issues addressed and based on law no 6 of 2018 concerning health quarantine. This research used descriptive analysis. Findings. The form of accountability for community actors who are not quarantined after returning from a trip abroad is regulated by Article 93 of the 2018 Act 06. Conclusion. The law states that anyone who does not comply with the Health Quarantine Regulations will be sentenced to one year in prison and/or a fine of up to IDR 100 million.